Historical Review Of Jambi Until The 17th Century - Arif Rahim (Information Technology and Science (ITScience), 2025)
The purpose of this study is to examine the origins of the Malay kingdom and the factors that influenced its emergence and existence in the context of the development of Jambi history until the 17th century. By digging and re-tracing and continuing with objective analysis of historical facts, this paper is expected to enrich the treasury of knowledge, as well as become a reflection and consideration for related agencies in making decisions or policies, especially if such matters are related to historical issues. This research is a literature review research based on the analysis of various conceptual information and qualitative and quantitative data from various reputable scientific articles. The results of this study are that the history of Asia between the 17th century is interpreted as a historical process that lasted more than a millennium, where the sea, fertile land, mountains and deserts are basic elements in a region where interactions occur between sailors, nomads and farmers. Such thinking allows for a principle where each element from various sets such as the Indian Ocean, Arabs, Indians, Chinese and so on are combined in the same historical pattern. This route is known as the silk route which functions to distribute products from east to west.